O Ensino de Ciências e a Aprendizagem em rede: Traços do Conectivismo no Brasil - Sossai, Rosiany Aguiar Coswosck (2020)
Considering the current digital age, the reflection on the systematization of learning, on the theoretical principles and processes contained therein, emerges, taking into account this fact, the present research seeks to make a theoretical reflection on C